GABRIELA MISTRAL, FEDERICO DE ONÍS Y LA PUBLICACIÓN DE DESOLACIÓN EN 1922. - Salomone, Alicia (Revista Chilena de Literatura, 2023)
This essay pursues a double goal. On the one hand, it aims to characterize the authorial staging of Gabriela Mistral by the year 1922, in the context of publication of her first poetry book, Desolación. On the other hand, it inquires into the process that led to the first edition of the book, which did not occur in Chile but in New York City (USA) due to the Spanish philologist Federico de Onís' mediation. The study's methodology shifts the focus from the poetic writing analysis itself to the dynamics of the Ibero-American literary and cultural fields. In this way, this essay elaborates on the conditions that allowed Mistral to have her book published and to consolidate her authorial figuration as a Latin American poet and intellectual of international relevance between the decades of 1920 and 1950.